Preparation of low-radioactive high-purity enriched 100MoO3 powder for AMoRE-II experiment - Yeon, Hyojin; Choe, JunSeok; Gileva, Olga; Hahn, Kevin Insik; Kang, Woon Gu; Kim, Go Woon; Kim, Hong Joo; Kim, Yena; Kim, Yeongduk; Lee, Eun Kyung; Lee, Moo Hyun; Leonard, Douglas S.; et al. (Frontiers in Physics, 2023)
This paper describes preparing radiopure molybdenum trioxide powder enriched with Mo-100 isotope for the AMoRE-II experiment. AMoRE-II, the second phase of the AMoRE experiments, will search for the neutrinoless double-beta decay (0νDBD) of the 100Mo isotope using over 100 kg of 100Mo embedded in 200 kg of ultra-pure Li2100MoO4 bolometric crystals. Efficient purification technology was developed and adapted to purify 100MoO3 powder with a 5 kg per month production capacity. Based on the ICP-MS analysis of purified powder, the 232Th and 238U were reduced to <9.4 μBq/kg and <50 μBq/kg, respectively. The concentrations of potassium, transition metals, and heavy metals were lower than 1 ppm. HPGe counting confirmed the reduction of progenies from the 232Th and 238U decay chains, reporting upper limits of <27 μBq/kg for 228Ac and <16 μBq/kg for 228Th. The 226Ra activity was acceptable at 110 ± 30 μBq/kg. In the last 3 years, 100 kg of pure 100MoO3 powder was produced. The production yield for the final purified product was above 90%, while irrecoverable losses were under 1.5%, and all by-products could be recycled further.